(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Back ground: Abdominal tuberculosis is common in Bangladesh and there is a national guide line for its management, which includes six months course of anti tubercular therapy (ATT). This study was done to evaluate the treatment outcome of abdominal tuberculosis following national guide line. Materials and Methods: This prospective study of descriptive nature was done between November 2009 to October 2010 at the department of Medicine, Sir Salimullah Medical College, Mitford hospital, Dhaka, Bangladesh. Total 6 months ATT was given to the selective 50 patients of abdominal tuberculosis following national guide line and out come measurement was done after completion of treatment. Result: Five patients died out of 50 patients during the course of treatment. The range of age was 13-70 years and mean ± SD = 33.2 ± 14.77 and male female ratio was o.72:1. Out of 50 patients 17(34%) patients had Intestinal TB, 24(48%) had Peritoneal TB, 2(4%) had abdominal lymph node TB, and 7(14%) had other types. Three patients of peritoneal TB patient died while rest 2 patients died were diagnosed as intestinal TB. Out of 45 patients who survived, 43(95.6%) improved and 2(4.4%) did not improve. Out of 15(33.3%) intestinal TB patients, 14(31.1%) improved and 1(2.2%) did not improved. Out of total 21(46.7%) peritoneal TB, 20(44.4%) improved and 1(2.2%) did not improve. Remaining 2(4.4%) abdominal lymph node TB, all were improved. In other variety cases (15.6%), all improved. Conclusion: Total 6 months regimen of ATT recommended by national guide line is proved as a complete and effective treatment course of abdominal tuberculosis. J Bangladesh Coll Phys Surg 2016; 34(2): 76-84